Characterization of Reflective TN-LCD, Tuned in Phase-Only Modulation and to Six Wavelengths - Rueda, Jorge Enrique; Romero, Ana Ludia; Guerra, Luis Alfonso (Photonics Letters of Poland, 2010)
We present the results of the characterization of a liquid crystal spatial modulator LCR2500. The phase modulation ratio versus applied voltage and six wavelengths was determined. The basic experimental arrangement is a Mach-Zehnder interferometer, where one mirror is a LCR2500. We found the modulation exceeding 2pi radians. The method eliminates errors in the phase due to a mechanical noise. Full text: PDF References: E. Badosa et al., "Complex modulation characterization of liquid crystal devices by interferometric data correlation", et al., Meas. Sci. Technol. 8, 764 (1997). [CrossRef] I. Moreno et al., "Transmission and phase measurement for polarization eigenvectors in twisted-nematic liquid crystal spatial light modulators", et al., Opt. Eng. 37, 3048 (1998). [CrossRef] T. Kelly et al., "Wavelength dependence of twisted nematic liquid crystal phase modulators", et al., Opt. Comm. 156, 252 (1998). [CrossRef] A. Lizana et al., "Time fluctuations of the phase modulation in a liquid crystal on silicon display: characterization and effects in diffractive optics", et al., Opt. Exp. 16(21), 16721. (2008). [CrossRef] J. Coy, M. Zaldarriaga, D. Grosz, O. Martínez, "Characterization of a liquid crystal television as a programmable spatial light modulator", Opt. Eng. 35, 15 (1996). [CrossRef] A. Márquez et al., "Characterization of edge effects in twisted nematic liquid crystal displays", et al., Opt. Eng. 39, 3301 (2000). [CrossRef] J. Davis, D. Allison, K. D'Nelly, I. Moreno, "Ambiguities in measuring the physical parameters for twisted-nematic liquid crystal spatial light modulators", Opt. Eng. 38, 705 (1999). [CrossRef] J. Pezzaniti, R. Chipman, "Phase-only modulation of a twisted nematic liquid-crystal TV by use of the eigenpolarization states", Opt. Lett. 18, 1567 (1993). [CrossRef] J. Davis, I. Moreno, P. Tsai, "Polarization Eigenstates for Twisted-Nematic Liquid-Crystal Displays", Appl. Opt. 37(5), 937 (1998). [CrossRef] A. Márquez et al., "Quantitative prediction of the modulation behavior of twisted nematic liquid crystal displays based on a simple physical model", et al., Opt. Eng. 40, 2558 ( 2001). [CrossRef] J. Nicolás, J. Campos, J. Yzuel, "Phase and amplitude modulation of elliptic polarization states by nonabsorbing anisotropic elements: application to liquid-crystal devices", Opt. Soc. Am. A 19, 1013 (2002). [CrossRef] A. Márquez, C. Cazorla, M. Yzuel, J. Campos, "Characterization of the retardance of a wave plate to increase the robustness of amplitude-only and phase-only modulations of a liquid crystal display", J. Mod. Opt. 52, 633 (2005). [CrossRef] L. Bougrenet, L. Dupont, "Complex amplitude modulation by use of liquid-crystal spatial light modulators", Appl. Opt. 36, 1730 (1997). [CrossRef] D. Berreman, "Optics in smoothly varying anisotropic planar structures: Application to liquid-crystal twist cells", J. Opt. Soc. Am 63, 1374 (1973). [CrossRef] K. Lu, B. Saleh, "Theory and design of the liquid crystal TV as an optical spatial phase modulator", Opt. Eng. 29, 240 (1990). [CrossRef] A. Yariv, P. Yeh, Optical waves in crystals (New York, John Wiley & Sons 1984). I. Khoo, Liquid crystals (New York, John Wiley & Sons 2007). [CrossRef] Takeda et al., "Fourier-transform method of fringe-pattern analysis for computer-based topography and interferometry", et al., J. Opt. Soc. Am. 72, 156 (1982). [CrossRef]